Reconstructing Conservation: Finding Common Ground - Minteer Ben A (Island Press, 2003)
In the 1990s, influenced by the deconstructionist movement in literary theory and trends toward revisionist history, a cadre of academics and historians led by William Cronon began raising provocative questions about ideas of wilderness and the commitments and strategies of the contemporary environmental movement. While these critiques challenged some cherished and widely held beliefs -- and raised the hackles of many in the environmental community -- they also stimulated an important and potentially transformative debate about the conceptual foundations of environmentalism.